Generalised additive model of DIR based on region, monsoon and state in Peninsular Malaysia - Che Him, Norziha; Yusof, Yusliandy; Samat, Nor Azah (2019)
A generalised additive model (GAM) framework for dengue incidence rate (DIR) as a response in Peninsular Malaysia for three areas which as region, monsoon and state has been adopted in this study. A spatio-temporal series of 1296 observations with the following explanatory variables; state, latitude and longitude of state capital, land area of state, year, month, total dengue cases, estimated state population pertaining to the year, population density of state, maximum, minimum and average monthly rainfall, maximum, minimum and average monthly temperature, monthly number of rainy days and Nino 4. Result presents three basis model with statistically significant explanatory variables consist of mean rainfall (current month and lag 3-month), mean temperature (current month and lag 1-month), number of rainy day (current month and lag 3-month), Nino 4 (lag 6-month), DIR (lag 3-month) and interaction between temperature lag 1-month and Nino 4 (lag 6-month), population, population density, year, month, monsoon area, state and region. Model 1, Model 2 and Model 3 with the lowest deviance, AIC and BIC are the best models of DIR that successfully developed for three areas mentioned.